Wyjątkowość fenomenu harcerskiego wychowania - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The world scout movement, including the Polish scout movement refers to a lesser or even to an orthodox extent to the pedagogical ideas and assumptions of Scouting by Robert Stephenson Baden-Powell and the successors of his pedagogics. In the article I respond to the question, to what extent does contemporary pedagogical thought refer to the phenomenon of scout movement education? Can we speak of the pedagogy of scouting or rather of scouting pedagogics? These issues cannot be solved solely on the level of normative models if one would not reach to former studies without indicating the necessity of conducting a scientific turn in this regard.